2014
DOI: 10.1016/j.biopsycho.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased insula coactivation with salience networks in insomnia

Abstract: Insomnia is among the most prevalent and costly of all sleep-related disorders. To characterize the neural mechanisms underlying subjective dysfunction in insomnia, we examined brain activity in 17 female insomniacs and 17 female healthy controls using simultaneous functional magnetic resonance imaging (fMRI) and electroencephalography (EEG) while they were resting and while they were trying to fall asleep. In examining the dynamic regional activity within intrinsic brain networks, we found that, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
135
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(155 citation statements)
references
References 48 publications
16
135
3
1
Order By: Relevance
“…Similarly, selective functional disconnection between the right anterior insula and the medial prefrontal cortex was correlated with the severity of the OSA in a very recent study, whilst the functional disconnection between the insula and the posterior cingulate cortex was correlated with depressive scores and working memory performance of patients with OSA (Zhang et al, 2015). Of other sleep disorders, patients with insomnia have also been shown to have a greater involvement of the anterior insula, as well as insula BOLD correlation with EEG gamma frequency power during rest (Chen et al, 2014). Moreover, this increased involvement of the anterior/ventral insula was associated with negative affect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, selective functional disconnection between the right anterior insula and the medial prefrontal cortex was correlated with the severity of the OSA in a very recent study, whilst the functional disconnection between the insula and the posterior cingulate cortex was correlated with depressive scores and working memory performance of patients with OSA (Zhang et al, 2015). Of other sleep disorders, patients with insomnia have also been shown to have a greater involvement of the anterior insula, as well as insula BOLD correlation with EEG gamma frequency power during rest (Chen et al, 2014). Moreover, this increased involvement of the anterior/ventral insula was associated with negative affect.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this increased involvement of the anterior/ventral insula was associated with negative affect. For instance, it has been suggested that here aberrant activation of the insula in arousal networks may underlie the misperception of sleep quality and subjective distress in insomnia (Chen et al, 2014). Given that insomnia and sleep apnea frequently co-exist (Luyster et al, 2010), it is tempting to postulate that recently highlighted divergent results of subjective versus objective complaints in OSA patients may also be a reflection of similar misperception and/or interoception of variety of bodily and cognitive functions in a subgroup of patients with OSA (Rosenzweig et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be mentioned a study using simultaneous fMRI and EEG by Chen, Chang, Glover, and Gotlib (2014) concerned with resting-states study on insomnia. They analyzed the functional connectivity of 17 PI patients and 17 healthy control participants during rest and during the time the participants tried to fall asleep.…”
Section: The Default-mode Networkmentioning
confidence: 98%
“…[29][30][31][32] A literature review identified 3 restingstate fMRI studies in patients with insomnia that investigated functional connectivity in salience, emotional and memory networks. 16,33,34 However, none of these studies focused on betweengroup dif ferences in the DMN or investigated the association between DMN connectivity and objective sleep parameters.…”
Section: J Psychiatry Neurosci 2016;41(5)mentioning
confidence: 99%
“…6 The etiology of insomnia in the absence of any identifiable organic or psychiatric disorder is assumed to be multifac torial, involving cognitive factors (e.g., worry and rumina tion, selective attention for sleeprelated cues, dysfunctional attitudes and beliefs about sleep 7,8 ), maladaptive behaviours (e.g., extending time in bed or daytime napping 9 ) and in creased physiologic arousal. 10 From a neurobiological point of view, several subcortical and cortical regions, including the ascending reticular activating system, amygdala, hippo campus, caudate nucleus, anterior cingulate cortex (ACC), in sula and frontal cortex, [11][12][13][14][15][16][17][18][19][20] are thought to be involved in the pathophysiology of night and daytime symptoms in patients with insomnia.…”
Section: Introductionmentioning
confidence: 99%